Nexus between Iraqi SMEs cloud computing adoption intention and firm performance: moderating role of risk factors - Ali Salah Alasady; Hayder Salah Hashim; Wid Akeel Awadh (Institute of Advanced Engineering and Science, 2023)
Cloud computing has been adopted in many developing nations, namely Iraq and Ghana, for its multiple benefits. Nonetheless, there is a dearth of studies on cloud computing adoption in developing nations. This study aims to investigate the factors influencing cloud computing adoption among Iraqi small and medium-sized enterprises (SMEs) and the implication of cloud computing on the SME firm performance. The diffusion of innovation (DOI) theory served as the foundation for the research model. Primary data from 396 SMEs were analysed using the structural equation modelling (SEM) approach through SmartPls 3.0 software for model testing. Resultantly, the use of cloud computing enhances firm performance. The technological factor also positively affects firm performance and cloud computing. The findings provide cloud service providers, managers, and government regulators with important recommendations to encourage the adoption and effective implementation of cloud computing in Iraq.